Managing Critical Infrastructure Risks - Linkov, Igor; Wenning, Richard J.; Kiker, Gregory A. (NATO Science for Peace and Security Series C: Environmental Security, 2007)
At the beginning of each year, there is a deluge of top-10 lists on just about every subject you can imagine. A top-10 list of biggest news stories, best-selling books, most popular music and movies, richest companies, and best places to visit or live. It seems everyone has his or her own top-10 list, reflecting, perhaps, differences in regional, national, and cultural values. Companies and governments most often tend to focus their top-10 lists on economic priorities, or priorities related to national defense, security, public health, and new infrastructure. This year, 2007, was no exception. Yet, increasingly, we see governments, private organizations, and companies advocating a new type of prioritization. The complexity of societal change requires an enhanced capacity for scientific assessment, monitoring, and emer gency response. New uncertain and multifaceted risks and stressors as well as globalization and public pressure for decision transparency drive the need for a new framework for thinking about prioritization. This framework needs to reach beyond the realms of economics, world trade, and corporate management to include the environment, stakeholders, public preferences, and social goals. Moreover, corporations and individuals are not only interested in generic 10-best lists; they want lists tailored to their values, goals, and current economic and social state. For example, the U. S.